Pengaruh Motivasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada Atria Hotel Gading Serpong Kabupaten Tangerang - Wiranti Wiranti; Roni Fadli (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This research aims to determine the influence of motivation and physical work environment on employee performance at the Atria Hotel Gading Serpong, Tangerang Regency, both partially and simultaneously, The method used is quantitative, The objects of this research are 53 employees of the Atria Hotel Gading Serpong, Tangerang Regency, The sampling technique used saturated sampling and the sample obtained in this study was 53 respondents, Research Results of the hypothesis test obtained a value of tcount > ttable or (4.680 > 2.008), with a significance probability value of (0.001 < 0.050), Thus, H0 is rejected and H1 is accepted, meaning that there is a significant influence between motivation (X1) on employee performance (Y) partially, Hypothesis testing obtained a value of tcount > ttable or (6.969 > 2.008), with a significance probability value of (0.001 < 0.050), Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence between the physical work environment (X2) on employee performance (Y) partially, Hypothesis testing obtained a value of Fcount > Ftable or (24.602 > 3.180), Thus H0 is rejected and H3 is accepted, This means that there is a significant influence between motivation (X1) and physical work environment (X2) on employee performance (Y) simultaneously, simultaneously Keywords: Motivation, Physical Work Environment, Employee Performance.